2015
DOI: 10.1371/journal.pone.0143704
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Specialization in the Sugarcane Aphid Melanaphis sacchari

Abstract: Most aphids are highly specialized on one or two related plant species and generalist species often include sympatric populations adapted to different host plants. Our aim was to test the hypothesis of the existence of host specialized lineages of the aphid Melanaphis sacchari in Reunion Island. To this end, we investigated the genetic diversity of the aphid and its association with host plants by analyzing the effect of wild sorghum Sorghum bicolor subsp. verticilliflorum or sugarcane as host plants on the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…The surprising occurrence of sugarcane aphid on sorghum in 2013 has led to speculation about the source of the aphid, including the possibilities of a host plant shift from sugarcane to sorghum in North America or an existing biotype that prefers sorghum entering North America through wind-aided movement or human activities. The genetic diversity is just beginning to be understood (Nibouche et al 2015), and its capacity for long-range movement can be inferred by field observations and research on other aphids in North America (Irwin and Thresh 1988).
Fig.1.Occurrence of sugarcane aphid on sorghum in the United States, 2013.
…”
Section: Occurrence and Damage On Sorghum In The United States And Mementioning
confidence: 99%
“…The surprising occurrence of sugarcane aphid on sorghum in 2013 has led to speculation about the source of the aphid, including the possibilities of a host plant shift from sugarcane to sorghum in North America or an existing biotype that prefers sorghum entering North America through wind-aided movement or human activities. The genetic diversity is just beginning to be understood (Nibouche et al 2015), and its capacity for long-range movement can be inferred by field observations and research on other aphids in North America (Irwin and Thresh 1988).
Fig.1.Occurrence of sugarcane aphid on sorghum in the United States, 2013.
…”
Section: Occurrence and Damage On Sorghum In The United States And Mementioning
confidence: 99%
“… Position and nature of nucleotide substitutions in M . sacchari COI sequence from this study (haplotype H6), from published data (H1, H2, H3) [ 14 , 28 , 29 ], and from Genbank (H4 = JX051388, JX051389, JX051390; H5 = HQ112185, JX051402). …”
Section: Methodsmentioning
confidence: 99%
“…Similar to numerous other aphid studies, which report aphids exhibiting host plant specialization among their populations [ 10 13 ], a recent study has demonstrated the existence of sympatric sorghum and sugarcane biotypes in M . sacchari on Reunion Island (Indian Ocean) [ 14 ]. The occurrence of sympatric biotypes in other areas has been assessed, but not been found [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…], sorghum, and Johnsongrass, the distribution of multilocus lineages was influenced by geography but not host plant (Nibouche et al, 2014). Yet SCA collected on Reunion Island in 2007 to 2013 on sugarcane and wild sorghum have MLGs that were classified as multilocus lineage C that were host specific (Nibouche et al, 2015).…”
Section: Genotyping Of 49 Aphid Samples (Supplementalmentioning
confidence: 99%